PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN ALAT PERAGA FLUIDA DINAMIS UNTUK MENINGKATKAN HASIL BELAJAR - Alviando Stevani Mumu; Ferdy Dungus; Aswin Hermanus Mondolang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
Efficient and effective learning begins with effective planning. This study aims to create a problem-based physics learning device development product using dynamic fluid visual aids to improve student learning outcomes at SMA Negeri 1 Tompaso. This research uses the research and development (R & D) method by following the stages of Borg and Gall development research. After the device development product was made and tested for feasibility by material experts, media experts and learning device experts who stated that problem-based physics learning tools using Dynamic Fluids were valid and suitable for use in learning. Then before the learning activities are carried out, a pre-test is carried out to determine the students' initial abilities and at the end of the meeting a post-test is carried out to see if there is an increase in the average value of student learning outcomes after participating in learning using the developed learning tools. Based on the test results, it can be seen that there is an increase in the average value of student learning outcomes, which is 13,30. Based on the statistics testing criteria, which means that it can be concluded that there is a significant change in student learning outcomes of class XI MIPA 2 SMA Negeri 1 Tompaso after participating in learning using problem-based Physics learning tools using the Dynamic Fluids teaching aid developed by the researcher.